2006
DOI: 10.1128/jb.00418-06
|View full text |Cite
|
Sign up to set email alerts
|

Sau1: a Novel Lineage-Specific Type I Restriction-Modification System That Blocks Horizontal Gene Transfer into Staphylococcus aureus and between S. aureus Isolates of Different Lineages

Abstract: The Sau1 type I restriction-modification system is found on the chromosome of all nine sequenced strains of Staphylococcus aureus and includes a single hsdR (restriction) gene and two copies of hsdM (modification) and hsdS (sequence specificity) genes. The strain S. aureus RN4220 is a vital intermediate for laboratory S. aureus manipulation, as it can accept plasmid DNA from Escherichia coli. We show that it carries a mutation in the sau1hsdR gene and that complementation restored a nontransformable phenotype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
256
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 275 publications
(282 citation statements)
references
References 32 publications
14
256
1
3
Order By: Relevance
“…This confirmed our earlier hypothesis that each lineage has a unique sau1hsdS gene that encodes Sau1 restriction-modification specificity, which then contributes to the relatively independent evolution of each lineage (see Discussion) (Waldron & Lindsay, 2006). Sequencing revealed that sau1hsdS1 genes of ST151 (CC151), ST771 (CC133) and ST130 (CC130) have similar conserved regions to the human isolates, mainly at the short 59 end known otherwise as the proximal conserved region, but had novel variable regions predicted to code the binding region to specific DNA sequences (data not shown).…”
Section: Sau1 Restriction-modification Systemsupporting
confidence: 78%
See 4 more Smart Citations
“…This confirmed our earlier hypothesis that each lineage has a unique sau1hsdS gene that encodes Sau1 restriction-modification specificity, which then contributes to the relatively independent evolution of each lineage (see Discussion) (Waldron & Lindsay, 2006). Sequencing revealed that sau1hsdS1 genes of ST151 (CC151), ST771 (CC133) and ST130 (CC130) have similar conserved regions to the human isolates, mainly at the short 59 end known otherwise as the proximal conserved region, but had novel variable regions predicted to code the binding region to specific DNA sequences (data not shown).…”
Section: Sau1 Restriction-modification Systemsupporting
confidence: 78%
“…These sequenced strains are all from humans and correspond to lineages CC1, CC5, CC8 and CC30. The microarray was also designed to include spots corresponding to putative target recognition domain (TRD) regions of sau1hsd1 that show major sequence variation, as described by Waldron & Lindsay (2006). PCR products were printed in duplicate on GAPS slides (Corning).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations